Legal Protection of Victims of Artificial Intelligence Misuse in the Form of Deepfake Porn in Indonesian Law - Kinanty, Norma; Santoso, Bambang (MultiTech Publisher, 2024)
In the era of Society 5.0, which is better known as the era of technological maturity and humanity, this era emphasizes increasing the capacity and quality of human resources (HR) in all joints, especially the use of technology. Until now, there has not been a single regulation that specifically regulates artificial intelligence. For all criminal offenses related to AI, the applicable law is ITE Law Number 1 of 2024. Issues related to misuse, legal protection efforts for victims, and law enforcement for perpetrators of misuse of AI in the form of deepfake porn are essential because it is a violation of honor and reputation. It is hoped that in the future, the public can protect themselves from the potential misuse of this technology. Therefore, to be able to comprehensively interpret how legal protection for victims of AI misuse in the form of deepfake porn is provided, analytical and in-depth research is needed regarding the legal review of the misuse of artificial intelligence in Indonesian regulations.